Image-Guided Hydrodynamic Gene Delivery: Current Status and Future Directions - Kamimura, Kenya (Pharmaceutics, 2015)
Hydrodynamics-based delivery has been used as an experimental tool to express transgene in small animals. This in vivo gene transfer method is useful for functional analysis of genetic elements, therapeutic effect of oligonucleotides, and cancer cells to establish the metastatic cancer animal model for experimental research. Recent progress in the development of image-guided procedure for hydrodynamics-based gene delivery in large animals directly supports the clinical applicability of this technique. This review summarizes the current status and recent progress in the development of hydrodynamics-based gene delivery and discusses the future directions for its clinical application.